Effects of bovine colostrum supplementation on athletic performance – literature review - Świetlicka, Gabriela; Pietrzak, Maria; Pietraś, Paulina; Chawryło, Aneta; Łupina-Romaniuk, Marcela; Piecuch, Dominika; Stolarczyk, Michał; Kołodziejczyk, Julia; Oleksińska, Karolina; Pracoń, Karolina (Quality in Sport, 2026)
Background: Colostrum is the first milk produced by mammals after birth and contains numerous bioactive compounds, including immunoglobulins, growth factors, lactoferrin, cytokines, and antimicrobial peptides. Bovine colostrum is widely used as a dietary supplement and has been associated with immunomodulatory, anti-inflammatory, antimicrobial, and regenerative properties. In sports nutrition, it has been investigated for its potential role in supporting immune function, post-exercise recovery, gastrointestinal barrier integrity, and adaptation to exercise-induced stress. However, its effects on athletic performance and mechanisms of action remain debated. Aim: This review evaluates evidence on the effects of bovine colostrum supplementation on performance, recovery, gastrointestinal integrity, and selected immune parameters in athletes and physically active individuals. Material and methods: A narrative review of randomized controlled trials, experimental studies, systematic reviews, and meta-analyses was conducted using PubMed, Scopus, and Web of Science. Results: Current evidence suggests modest and context-dependent benefits, mainly for mucosal immunity, intestinal barrier function, inflammatory responses, and post-exercise recovery. Some studies reported favorable effects on salivary secretory IgA, intestinal permeability or injury markers, and selected biochemical indicators. However, direct effects on strength, endurance, body composition, and sport-specific performance remain inconsistent. Conclusions: Bovine colostrum may be considered a supportive nutritional strategy for selected athletes exposed to intensive training, endurance exercise, or immune and gastrointestinal stress. Further randomized controlled trials are needed to define optimal dose, duration, timing, and target populations.